TEACHING STUDENT SPEAKING SKILLS USING THE GUESS GAME SDIT Al-IHSAN - Rohimah, Ainur; Kiptiyah, Mariyatul (Jurnal Dedikasi Pendidikan, 2025)
This study aims to describe the use of guess game method in enhancing students' speaking skills at SDIT Al-Ihsan. This research uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that the use of guess games was able to increase students' active participation, self-confidence, and ability to use vocabulary and construct sentences in English. The learning atmosphere becomes more fun and interactive, so students are more motivated to speak without fear of making mistakes. Students who were initially passive began to be actively involved after being encouraged by the teacher and their peers. Social interaction between students also increased, strengthening cooperation and support during the learning process. Although some students had difficulty in conveying descriptions clearly, the teacher's guidance and examples helped them develop gradually. Based on the results of the study, it can be concluded that the guess game method is effectively used in learning English speaking skills at the elementary school level, especially in creating a supportive, fun, and meaningful learning environmenta